2012
DOI: 10.1590/s1414-32832012005000027
|View full text |Cite
|
Sign up to set email alerts
|

Letramento funcional em saúde: reflexões e conceitos sobre seu impacto na interação entre usuários, profissionais e sistema de saúde

Abstract: Letramento funcional em saúde (LFS) é o grau pelo qual os indivíduos têm a capacidade para obter, processar e entender informações básicas e serviços necessários para a tomada de decisões adequadas em saúde. O tema preocupa pesquisadores/profissionais da saúde/formuladores de políticas públicas. Sua natureza interdisciplinar, relacional e interacional indica que o LFS sofre a influência dos sistemas de saúde/educacional, mídia, família, ambiente de trabalho/comunidade/decisão política. Analisam-se conceitos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
54

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 31 publications
2
43
0
54
Order By: Relevance
“…Tal modelo é bastante citado e criticado por Almeida Filho (2010), Passamai et al (2012), Nuto et al (2006) e Souza (2001.…”
Section: Caracterização Dos Processos De Formação Durante a Trajetóriunclassified
“…Tal modelo é bastante citado e criticado por Almeida Filho (2010), Passamai et al (2012), Nuto et al (2006) e Souza (2001.…”
Section: Caracterização Dos Processos De Formação Durante a Trajetóriunclassified
“…5,6 FHL is cited in a report issued by the Ad Hoc Committee on Health Literacy for the Council on Scientific Affairs, from the American Medical Association (AMA), 7 as an expansion of HL, implying the operationalization (practical) of literacy in the concept itself. 8 The two terms are used interchangeably. 9 The term Functional Health Literacy is used in the present study as it is used in Brazilian studies identified in the literature of this area (health).…”
Section: Introductionmentioning
confidence: 99%
“…9 The term Functional Health Literacy is used in the present study as it is used in Brazilian studies identified in the literature of this area (health). 4,8 Studies have reported that FHL is a relatively new concept in the area of health promotion. 9,10 It is also considered an emerging field in the areas of education and health promotion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations